Detection of Candida auris and its antifungal susceptibility: first report from Bangladesh - Dutta, Subarna; Rahman, Md Hasibur; Hossain, Kazi Shakhawath; Haq, Jalaluddin Ashraful (IMC Journal of Medical Science, 2020)
Background and objectives: Candida auris is an emerging multidrug-resistant fungal pathogen that has been associated with nosocomial infections with a high mortality. The organism has been reported from several countries of the world except Bangladesh. The present study describes the presence of C. auris in clinical samples obtained from a large hospital of Dhaka city, Bangladesh. Materials and methods: The A total of 100 Candida species isolated from different clinical samples were purposively included in the present study. Samples were obtained from patients attending a 750 bed hospital of Dhaka city. C. auris was identified by growth characteristics, biochemical and carbohydrate assimilation test and further confirmed by polymerase chain reaction and sequencing using ITS1 and ITS2 targeting the conserved regions of 5.8S rRNA. Antifungal susceptibility of identified C. auris was performed by disk diffusion and minimum inhibitory concentration (MIC) methods. Results: Out of 100 Candida sp. tested, 21 isolates were identified as C. auris. Of the 21 C. auris, 14 (66.7%) were isolated from blood samples and the remaining 7 (33.4%) were from urine. Most of the C. auris isolated were from patients admitted in intensive care units. Out of 21 C. auris, 17 (81.0%), 7 (33.3%) and 3 (14.3%) were sensitive to amphotericin B, fluconazole and voriconazole respectively by disk diffusion method. Out of 14 fluconazole resistant isolates, 5 were susceptible dose-dependent (SS-D) by MIC method. Conclusion: The present study is the first report demonstrating the presence of C. auris in clinical samples obtained from a large hospital of Bangladesh. Majority of isolates showed resistance to fluconazole and variable susceptibility to other antifungal agents. Further study is suggested to find its true magnitude and its susceptibility pattern to a range of antifungal agents. Ibrahim Med. Coll. J. 2019; 13(2): 18-22